EXTREME SPECTRUM OF DYSGLYCAEMIA IN TWO SISTERS WITH CDKN1C MUTATION - Rusli, Nur Sabrina; Hui, Saw Shi; Majid, Naily Athirah Hamidun; Rahman, Muhammad Danial Abdul; Samingan, Nurshadia; Annie, Leong; Jalaludin, Muhammad Yazid; Zaini, Azriyanti Anuar (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND CDKN1C mutation is mainly associated with BeckwithWiedemann syndrome (BWS), an overgrowth disorder, and IMAGe syndrome, an undergrowth disorder. In both conditions, hypoglycaemia can be part of the presenting features. Defect in this gene has not been directly linked with diabetes; however, evidence supports the hypothesis that loss of CDKN1C function leads to increased beta cell proliferation and causes hypoglycaemia. Some hypotheses also suggest that overactivity of CDKN1C gene results in the opposite phenotype: decreased proliferation of beta cells leading to reduced insulin production and onset of diabetes. CASE We report two cases of Malay siblings who presented with dysglycaemia of opposite ends of the spectrum. Both siblings were not dysmorphic with normal BMI. The elder sister, now 21 years, presented at the age of 5 years with hyperglycaemic symptoms and was treated as type 1 diabetes. Her diabetes autoantibodies were negative. She has been on insulin with an average HbA1c of 8%. The younger sister presented at 16 years with frequent postprandial hypoglycaemia episodes associated with recurrent cramps and muscle weakness. Investigations showed hyperinsulinaemic hypoglycaemia with concurrent hypokalaemia. PET scan and MRI were negative for insulinoma. Oesophagogastroduodenoscopy did not find any suspicious gastrointestinal lesions. Munchausen by proxy was excluded. Her symptoms improved with oral diazoxide but not fully resolved. She is dependent on potassium supplements. Genetic testing on both sisters revealed same mutation at the CDKN1C gene, reported as variant of uncertain significance (VUS). CONCLUSION In our patients, CDKN1C mutation manifested with polar opposites of dysglycaemia. The molecular function of the gene in glucose homeostasis is yet to be defined.